2017
DOI: 10.1039/c6cp07340a
|View full text |Cite
|
Sign up to set email alerts
|

Probing ice VII crystallization from amorphous NaCl–D2O solutions at gigapascal pressures

Abstract: The high density amorphous solution NaCl·10.2D2O crystallises at 260 K as almost pure ice VII during annealing at gigapascal pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 38 publications
(41 reference statements)
3
30
0
Order By: Relevance
“…We have found that concentrated NaCl solutions amorphise at ambient pressure in a high density structure similar to the HDA form of pure water [36,44], in agreement with similar observations for LiBr and LiCl solutions [45,46]. The samples produced with this device have been used in high pressure neutron diffraction studies [36,47].…”
Section: Fraction Of Amorphous Materialssupporting
confidence: 78%
“…We have found that concentrated NaCl solutions amorphise at ambient pressure in a high density structure similar to the HDA form of pure water [36,44], in agreement with similar observations for LiBr and LiCl solutions [45,46]. The samples produced with this device have been used in high pressure neutron diffraction studies [36,47].…”
Section: Fraction Of Amorphous Materialssupporting
confidence: 78%
“…5H2O is a clathrate similar to ice-VII but with volume expanded to 88.1 Å 3 (43) and part of the alkali-halide residing on site 6d.…”
Section: Methodsmentioning
confidence: 99%
“…We use V0, B0, and B0' of pure ice-VII from Frank et al (26). The effect of dissolved ionic species such as NaCl, KCl, and LiCl on the volume of ice-VII has been studied but different groups come to contrary conclusions whether alkali halides induce positive (27,37,43) or negative (26) excess volume.…”
Section: Estimation Of the Current Inclusion Pressuresmentioning
confidence: 99%
“…This view was challenged almost 10 years ago, by the discovery of a high-pressure ice phase based on the ice VII lattice [16] including Li and Cl ions in the large fraction of one ion pair for each six water molecules (R = water molecules/ion pairs = 6) and showing structural and physical properties different from those of pure ice. Subsequently, LiBr and NaCl [18,19] have also been shown to form salty ice crystals under high pressure for R values close to their eutectic composition.…”
Section: Introductionmentioning
confidence: 99%
“…by crystallization upon temperature annealing of amorphous water-salt solutions at high pressure [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%